Pengaruh Polaritas Pelarut terhadap Efisiensi Ekstraksi Total Alkaloid dari Daun Rambai (Sonneratia caseolaris) - Siti Masodah; Niken widiastuti hariati; Nurmeily Rachmawati; Serli Dwi Nurhayati (Jurnal Skala Kesehatan, 2026)
Diabetes mellitus is a non-communicable disease with a rising prevalence. Alkaloids are known to have antidiabetic effects by inhibiting carbohydrate-digesting enzymes and enhancing glucose metabolism. This study aimed to determine the total alkaloid content of Rambai leaves (Sonneratia caseolaris) using solvents with different polarities: ethanol and n-hexane. A descriptive study was conducted using the maceration method, followed by quantification of alkaloids with the quinine equivalent method using a UV-Vis spectrophotometer. Results showed that ethanol extract produced a higher yield (17.72 g; 35.44%) compared to n-hexane (3.09 g; 6.18%). The alkaloid content in the ethanol extract was 414.43 Âµg/g, nearly twice that of n-hexane (217.09 Âµg/g). Statistical analysis revealed a significant difference (p<0.001). Ethanol was proven to be more effective in extracting polar to semi-polar alkaloid compounds. The high alkaloid content indicates Rambai leaves have potential as a natural source for diabetes therapy. These findings provide a foundation for future product development and preclinical trials.